DIGITAL-BASED GRATITUDE INTERVENTION IN ADOLESCENCE AT THE RUMAH PIATU MUSLIMIN FOUNDATION ORPHANAGE - Johan Satria Putra; Ratih Arruum Listiyandini; Chandradewi Kusristanti (LP2M Universitas Ibrahimy, 2026)
As a vulnerable group, adolescents living in orphanages tend to experience various psychological issues, such as difficult regulating emotions, a lack of self-acceptance, and low life satisfaction. It has been observed among foster children and adolescence at the Yayasan Rumah Piatu Muslimin Orphanage in Jakarta. The assessment results showed that obstacles to life satisfaction triggered negative emotions and anxiety about the future. Therefore, a digital gratitude intervention was developed to increase positive emotions and life satisfaction. This intervention involved two stages, with 10 children aged 12–17 participating. The first stage focused on gratitude education, while the second stage used a digital visual and reflective approach involving photography, writing, and verbal expression. Evaluations measured using the Skala Syukur, Positive and Negative Affect Schedule (PANAS), and the Satisfaction With Life Scale, conducted through pre-test and two post-tests, revealed an increase in positive emotions and life satisfaction, as well as a decrease in negative emotions, following the intervention. Participants emphasized the need for better time management and more engaging material to optimize program outcomes.